Prescription pattern of non-steroidal anti-inflammatory drugs among patients admitted with fever in a tertiary hospital - Cherumanalil, Jeeja Mathummal; Thayyil, Jayakrishnan; Habeebulla, Madeeha; Louis, Jobin; Vishwanath, Vimal (International Journal of Basic & Clinical Pharmacology, 2023)
Background: WHO estimates that more than half of all medicines are prescribed, dispensed or sold inappropriately. Nonsteroidal anti-inflammatory drugs are a group of drugs that are commonly prescribed for the treatment of fever associated with pain and inflammation. The objective was to assess the prescribing pattern of NSAIDs in fever patients. Along with this, we looked at the clinical indications for prescribing and the pattern of prescribing with respect to use of generic or trade names. Methods: This observational study was conducted in a tertiary care teaching hospital in Malappuram district of Kerala, India by extracting data of inpatients retrospectively from medical records for a six-month period. The reported prevalence of NSAID use in previous study was 20%, with a relative precision of 18% the sample size required was 500. The data was analyzed and expressed as absolute numbers and/or percentages. Results: Out of these 500 patients, Dengue fever was the most common diagnosis (86.6%) followed by Typhoid (2.8%) and Leptospirosis (2.4%). Among these, 392 (78.4%) received any of the NSAIDs. The most commonly prescribed drug was Paracetamol (77.04%). Among to the prescriptions, 91.7% were prescribed with generic names. As concomitant medications, antibiotics were prescribed at 21.2% cases, gastro protective agents were prescribed to 24.23% and vitamins were prescribed in 72.6% cases. Conclusions: This study has shown that the prescribing, usage and preferences of NSAIDs practiced rationally. No over use, under use or misuse of drugs was noticed.